2021
DOI: 10.1007/s11553-021-00883-4
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheitskompetenz von Mitarbeitenden

Abstract: Zusammenfassung Hintergrund Um mit den zunehmenden Belastungen und Herausforderungen umgehen zu können, wird Gesundheitskompetenz (GK) im Alltag und Arbeitskontext immer wichtiger. Ziel der Arbeit Das Ziel dieser Arbeit ist es, eine Analyse der selbsteingeschätzten GK der Mitarbeitenden eines Unternehmens der verarbeitenden Metallindustrie durchzuführen und auf deren Grundlage Handlungsempfehlungen zur Stärkung der GK herauszustellen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
0
0
1
Order By: Relevance
“…Moreover, our surveyed students with low health literacy were more vulnerable to specific health issues and critical health-related behavior. This finding seems to be in line with some studies that have found associations between health literacy levels and various health indicators [44,72,74,75]. Our results suggest that some students already have health literacy that enables them to understand, evaluate, and use health-related information.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our surveyed students with low health literacy were more vulnerable to specific health issues and critical health-related behavior. This finding seems to be in line with some studies that have found associations between health literacy levels and various health indicators [44,72,74,75]. Our results suggest that some students already have health literacy that enables them to understand, evaluate, and use health-related information.…”
Section: Discussionsupporting
confidence: 92%
“…B. [9,16,32]). Da das Ziel der vorliegenden Studie nicht die Erhebung repräsentativer Daten war, wurde aufgrund der kleinen Stichprobengröße kein begleitender Fragebogen eingesetzt.…”
Section: Limitationenunclassified